2009
DOI: 10.1017/s0022377809007971
|View full text |Cite
|
Sign up to set email alerts
|

Waves in Rydberg plasmas

Abstract: Abstract. We define as the Rydberg plasma the weakly ionized gas produced in magneto-optical traps. In such a plasma, the neutral atoms can be excited in Rydberg states. Wave propagation in Rydberg plasmas and the mutual influence of plasma dispersion and atomic dispersion are considered. New dispersion relations are established, showing new instability regimes and new cut-off frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…In recent years, ultracold plasmas, produced by photoionization of laser-cooled atoms [1][2][3][4] or molecules [5], have opened up new avenues for studying various plasma physics phenomena, ranging from collective behavior [6][7][8][9][10][11][12][13], plasma expansion [14][15][16][17][18][19] and strong correlations [20][21][22][23][24][25][26][27][28][29] through to low-energy atomic processes [30][31][32][33][34][35][36][37]. Experimentally, these studies rely on the ability to probe the time-evolving state of the plasma that is characterized, e.g., by the density and temperature of the different plasma constituents.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, ultracold plasmas, produced by photoionization of laser-cooled atoms [1][2][3][4] or molecules [5], have opened up new avenues for studying various plasma physics phenomena, ranging from collective behavior [6][7][8][9][10][11][12][13], plasma expansion [14][15][16][17][18][19] and strong correlations [20][21][22][23][24][25][26][27][28][29] through to low-energy atomic processes [30][31][32][33][34][35][36][37]. Experimentally, these studies rely on the ability to probe the time-evolving state of the plasma that is characterized, e.g., by the density and temperature of the different plasma constituents.…”
Section: Introductionmentioning
confidence: 99%
“…with ω 2 P = q 2 N e /(mε 0 ) the plasma frequency and N e the number density of plasma electrons. Result (12) quantifies the physical effects that we have discussed in the previous section. To explain this we first remark that objects of the form v * ⊗ v for some vector v are (proportional to) projectors that map any vector to its component parallel to v. Hence, in absence of plasma ( ↔ M= 0), the roots of Eq.…”
Section: Theoretical Resultsmentioning
confidence: 86%
“…In the optical regime these experiments are complemented by absorption imaging methods to determine the ion velocity distribution [10,11]. If radiation propagates through a gas of Rydberg atoms [12] wave instabilities can occur due to energy transfer between excited Rydberg states and plasma electrons, and electrostatic waves [13]. Lu et al [14] suggested microwaves as a tool to measure the recombination rate of electrons and ions in ultra-cold neutral plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…We know that for transverse waves, the amplitude of density perturbations is equal to zero. In this composite medium, it can easily be shown that the frequency ω and the wave vector k = kẑ are related by [11] …”
Section: Basic Equationsmentioning
confidence: 99%
“…where c is the speed of light in vacuum; N is the index of refraction; ω pe = (4πn 0 e 2 /m e ) 1/2 is the electron plasma frequency; n 0 is the electron number density; e is the magnitude of the electron charge; m e is the electron mass, β = f a N a D/n 0 has the dimension of time; f a is the oscillator strength [11]; N a is the density of the neutral atoms; D is the population coefficient; and ω a is the radiation transition frequency. Equation (1) has been simply obtained from the Maxwell equations including the electron current and the contribution to the Maxwell equation because of the polarization vector, which equals the product of the atomic susceptibility, the neutral number density and the electromagnetic wave electric field.…”
Section: Basic Equationsmentioning
confidence: 99%